Hipnoterapi: Proses dan Dampak Religiulitas dalam Menyelesaikan Kasus Kenakalan Seorang Remaja - Rohimi Rohimi (Institut Agama Islam Negeri Bengkulu, 2019)
This study examines the process of rehabilitation of juvenile delinquent muslim clients in the practice of hypnotherapy. This study uses qualitative methods or field research, where the researchers immediately jumped into the research location located at the Institute of Indonesian Hypnotherapist Association (IHI) Yogyakarta. The method of data collection in this study through in-depth interviews, observation and documentation. The results of this study that the rehabilitation process of juvenile delinquent clients in the practice of hypnotherapy uses several methods of hypnotherapy that are used to restore the nature of a child to be a good person and stop doing negative things. Some methods of rehabilitation of juvenile delinquency clients carried out in the practice of hypnotherapy, namely (a) suggestibility tests and per-induction interviews, collect information related to client problems to facilitate the rehabilitation process (b) induction, entering the client's consciousness to the subconscious mind. easy to rehabilitate from the problems faced by clients (c) deepening, where teenage clients have gone through an unconscious stage and from the guiding stage to being given motivation to blend positively (d) depth level test, the stage of seeing a result of rehabilitation of juvenile delinquency clients (e) termination, the stage of returning a conscious mind of a client.